Apoptotic cells for treatment of acute respiratory distress syndrome associated with COVID-19 - van Heerden, Peter Vernon; Abutbul, Avraham; Naama, Ahmad; Maayan, Shlomo; Makram, Nassar; Nachshon, Akiva; abu Jabal, Kamal; Hershkovitz, Oren; Binder, Lior; Shabat, Yehudit; Reicher, Barak; Mevorach, Dror (Frontiers in Immunology, 2023)
Background. Hyper-inflammatory immune response, a hallmark of severe COVID-19, is associated with increased mortality. Acute respiratory distress syndrome (ARDS) is a common manifestation. We undertook two phase I/II studies in five and then 16 subjects with severe/critical COVID-19 to assess the safety and preliminary efficacy of apoptotic cells (Allocetra™-OTS, Enlivex Therapeutics), a cellular immunomodulatory therapy that reprograms macrophages to reduce hyper-inflammatory response severity. Methods. Eligible patients presenting to the Emergency Room with severe COVID-19 and respiratory dysfunction received one intravenous administration of Allocetra™-OTS and were monitored for adverse events (AEs) for 28 days. The primary aim was to determine the safety profile of treatment; secondary aims were recovery from ARDS, intensive care unit (ICU) and hospital length-of-stay, and mortality. Immune modulator markers were measured to elucidate the mechanism of action of Allocetra™-OTS. Results. 21 patients with severe-critical COVID-19 of Gamma, Alpha and Delta variants, were treated with a single dose of apoptotic cells. 19/21 patients had mild-to-severe ARDS at presentation. Median age was 53 years, 16/21 were males, 16/21 were overweight/obese. No serious related adverse events (SAEs) were reported. All 21 study subjects survived to day 28 (end of study); 19/21 recovered completely. Comparable mortality rates at the hospital were 3.8%−8.9% for age- and gender-matched patients, and 39%−55% for critical patients. Recovering patients exhibited rapid ARDS resolution and parallel resolution of inflammation markers and elevated cytokines/chemokines. Conclusion. In patients with severe/critical COVID-19 associated with ARDS, Allocetra™-OTS was safe, well-tolerated, and showed promising results for resolution of respiratory failure and inflammation. Trial registration. ClinicalTrials.gov Identifiers: NCT04513470, NCT04590053. https://clinicaltrials.gov/ct2/show/study/NCT04513470, https://clinicaltrials.gov/ct2/show/study/NCT04590053.